Classification of Majene Regency Landslide Prone Areas Using Geographic Information System and Storie Index: Klasifikasi Daerah Rawan Tanah Longsor Kabupaten Majene Menggunakan Sistem Informasi Geografis dan Metode Indeks Storie - Indadzil A. P. Santoso; Aulia L. P. Wibowo; Cut L. Zulfa; Naufal N. Siregar; Rangga Adiprima Sudisman (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2022)
On January 14, 2021, several villages in Majene Regency suffered landslides triggered by a M6.2 earthquake. The study’s aim is to use the Index Storie model approach, remote sensing data, and Geographic Information Systems (GIS) to map the distribution of landslide-prone areas as a mitigation basis in Majene Regency to reduce the potential for future landslide disasters. The level of landslide potential was determined based on slope conditions, soil types, rainfall, land use types, and potential earthquake risk. In general, morphological conditions in Majene Regency are dominated by slopes that are still covered in forests and receive relatively low rainfall, resulting in low landslide potential if seismic potential factors are not taken into account. Based on the results of an analysis that considers slope factors and potential seismic risks, the results of a map that illustrates the risk of landslide are quite high in several areas, are Malunda District, Ulumanda District, and Tubo Sendana District.